2020
DOI: 10.3390/cancers12061520
|View full text |Cite
|
Sign up to set email alerts
|

National Policies to Prevent and Manage Cervical Cancer in East African Countries: A Policy Mapping Analysis

Abstract: Policy mapping is used to provide evidence on effective interventions and highlight the necessary refinements of health policies. The goal of this work is to carry out legal mapping to identify and assess health policies for the prevention and management of cervical cancer in East African countries. Cervical cancer, as a largely preventable disease, is the cause of most cancer deaths among women in East African countries. Legal documents were searched uniformly from government websites, national cancer institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…The incidence and mortality from cervical cancer is 26 and 18 per 100,000, respectively [15]. These numbers are likely to be under-reported given the limited access to screening services and low level of awareness of cervical cancer [16]. Studies in Ethiopia have shown that the magnitude of precancerous cervical lesions among women ranges from 7% to 28% [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence and mortality from cervical cancer is 26 and 18 per 100,000, respectively [15]. These numbers are likely to be under-reported given the limited access to screening services and low level of awareness of cervical cancer [16]. Studies in Ethiopia have shown that the magnitude of precancerous cervical lesions among women ranges from 7% to 28% [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…This study suggests that majority, over 72%, of cervical cancer attributable to HPV in North and East Africa could be prevented by vaccine, especially by using quadrivalent and nonavalent vaccines. Since 7 out of 12 countries are currently providing HPV vaccination at no cost for girls in East Africa, there is a higher chance of eliminating cervical cancer in the sub-continent by 2090 (Brisson et al, 2020;Njuguna et al, 2020). The findings of this study show that though nonavalent vaccine could prevent approximately 52% of cervical cancer attributable to HPV in Central, Western and Southern Africa, a tangible number of cervical cancer will still be observed in the sub-regions due to high prevalence of non-vaccine hrHPV.…”
Section: Discussionmentioning
confidence: 99%
“…This study suggests that majority, over 72%, of cervical cancer attributable to HPV in North and East Africa could be prevented by vaccine, especially by using quadrivalent and nonavalent vaccines. Since 7 out of 12 countries are currently providing HPV vaccination at no cost for girls in East Africa, there is a higher chance of eliminating cervical cancer in the sub-continent by 2090 [9,27]. The findings of this study show that though nonavalent vaccine could prevent approximately 52% of cervical cancer attributable to HPV in Central, Western and Southern Africa, a tangible number of cervical cancer will still be observed in the sub-regions due to high prevalence of non-vaccine hrHPV.…”
Section: Discussionmentioning
confidence: 99%